2015
DOI: 10.1109/memc.2015.7098517
|View full text |Cite
|
Sign up to set email alerts
|

Conducted Interference, Challenges and Interference Cases

Abstract: T he chosen theme for this issue is Conducted Interference in Power Electronics. The attention paid to this area has been on the increase over many years due to the use of electron ic switching to condition power, e.g. for rectification, voltage level changes, etc. This causes high rates of change for voltage and current thus contributing significantly to EMC problems.Applications such as Smart Grids have brought electronic switch ing techniques into conventional power networks with the atten dant EMI problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 3 publications
0
50
0
Order By: Relevance
“…In order to detect current waveforms causing meter errors, four methods are developed and tested on the disturbing current signal depicted in Fig. 1a: 1) Since the rise time of the current waveform might be related to the cause of false static meter readings [1], [3], [4] the most straightforward indicator to detect such wave shapes is the calculation of their derivatives. Thus, the first method is the calculation of the dI/dt.…”
Section: Detection Algorithms Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to detect current waveforms causing meter errors, four methods are developed and tested on the disturbing current signal depicted in Fig. 1a: 1) Since the rise time of the current waveform might be related to the cause of false static meter readings [1], [3], [4] the most straightforward indicator to detect such wave shapes is the calculation of their derivatives. Thus, the first method is the calculation of the dI/dt.…”
Section: Detection Algorithms Comparisonmentioning
confidence: 99%
“…However, the use of more power electronics results in the generation of highly distorted currents, entering the distribution grid. In addition to the generated high frequency harmonics (between 2-150 kHz), some of these currents are characterized by sharp transitions with very short rise times which can cause EMI [1], [2]. Such phenomena, mainly observed when non-linear, fast switching loads are connected, can result in large errors in static electricity meters.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research it was shown that conducted EMI can result in faulty static meters readings. In photo voltaic (PV) systems high interference levels were caused by either the power drives of fans [3] or active infeed converters connected to PV systems [4], [5]. These interference levels resulted in lower readings of static meters.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been shown that significant errors occur when the meters are exposed to interference caused by home appliances. For photo voltaic (PV) systems, errors on the meters were caused by either the active infeed converters [3], [4] or the power drives of fans [5]. In these studies lower readings of the meters were encountered.…”
Section: Introductionmentioning
confidence: 99%